Effects of IL‐1β–Blocking Therapies in Type 2 Diabetes Mellitus: A Quantitative Systems Pharmacology Modeling Approach to Explore Underlying Mechanisms. (11th June 2014) - Palmér, R; Nyman, E; Penney, M; Marley, A; Cedersund, G; Agoram, B
Abstract : Recent clinical studies suggest sustained treatment effects of interleukin‐1β (IL‐1β)–blocking therapies in type 2 diabetes mellitus. The underlying mechanisms of these effects, however, remain underexplored. Using a quantitative systems pharmacology modeling approach, we combined ex vivo data of IL‐1β effects on β‐cell function and turnover with a disease progression model of the long‐term interactions between insulin, glucose, and β‐cell mass in type 2 diabetes mellitus. We then simulated treatment effects of the IL‐1 receptor antagonist anakinra. The result was a substantial and partly sustained symptomatic improvement in β‐cell function, and hence also in HbA1C, fasting plasma glucose, and proinsulin–insulin ratio, and a small increase in β‐cell mass. We propose that improved β‐cell function, rather than mass, is likely to explain the main IL‐1β–blocking effects seen in current clinical data, but that improved β‐cell mass might result in disease‐modifying effects not clearly distinguishable until >1 year after treatment. CPT: Pharmacometrics & Systems Pharmacology (2014) 3, e118; doi:10.1038/psp.2014.16 ; advance online publication 11 June 2014